The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.17212/1994-6309-2018-20.2-63-74
|View full text |Cite
|
Sign up to set email alerts
|

On the Participation of Hydrogen in the Formation of the Properties of Hypereutectic Al-Si Alloys

Abstract: Развитие современной аэрокосмической промышленности требует создания новых легких металлических материалов, которые обеспечат большую весовую отдачу деталей и стабильность

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…In the works [3,4,5,6] a new understanding of the philosophy of metallurgy, a new look at the formation of the dark and light in the nature and structure of metals, including cast iron (graphitedark and cementite -light) are considered. "...…”
Section: Research and Resultsmentioning
confidence: 99%
“…In the works [3,4,5,6] a new understanding of the philosophy of metallurgy, a new look at the formation of the dark and light in the nature and structure of metals, including cast iron (graphitedark and cementite -light) are considered. "...…”
Section: Research and Resultsmentioning
confidence: 99%
“…It was shown that the influence of the external environment is determined by the change in the ratio of the interstitial elements -hydrogen, nitrogen, oxygen and carbon -in the alloys. In articles [15][16][17] we showed that heat treatment in media with an increased content of hydrogen and nitrogen accelerates the course of phase transformations in aluminum and iron alloys, since it activates the diffusion of hydrogen in them.…”
Section: Introductionmentioning
confidence: 99%